Assessing the responses of tolerant papaya (Carica papaya L.) varieties to papaya ringspot virus (PRSV) infection and establishment of symptom severity rating scale for resistance screening (The Philippine Journal of Crop Science, 2012)
Sinta, a popular papaya hybrid and its female parental line Cariflora are considered Papaya ringspot virus (PRSV) tolerant varieties because although these varieties can be infected, the yields are not significantly reduced. However, the responses of Sinta and Cariflora whether resistance or tolerance to PRSV infection, have not yet been assessed and characterized. Knowledge on the responses of any variety to virus infection is important in designing strategies for the development and deployment of virus resistant varieties. Responses to PRSV infection was determined by comparing the development of PRSV infection on Sinta and Cariflora with the susceptible variety, Solo. Two-month old healthy seedlings were mechanically inoculated with PRSV, and the development of infection was observed weekly for 8 weeks under screenhouse conditions. Disease development was compared based on disease onset, disease progress, disease incidence, symptom severity, and virus titre in plant. Sinta had delayed disease onset and reduced symptom severity, while Califlora had delayed onset, lower Area under the disease progress curve (AUDPC), reduced disease incidence, and reduced symptom severity. However, there was no significant decrease of virus titre as measured by Enyme-linked Immunosorbent. Assay in both varieties, indicating that these two varieties are indeed tolerant but not resistant. Based on disease index, Sinta and Cariflora were considered as moderately-tolerant. A symptom severity rating scale for resistance screening was established in this study. The rating scale represented the pattern of symptom development indicating different degrees of symptom severity starting from mottling, then mosaic, followed by mosaic accompanied by leaf deformation, and lastly by mosaic accompanied with leaf deformation and shoe stringing. The method and the parameters measured for PRSV resistance/tolerance screening under screenhouse conditions are discussed.